2014
DOI: 10.1007/s40279-014-0244-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Triathlon Training and Racing on Athletes’ General Health

Abstract: Although the sport of triathlon provides an opportunity to research the effect of multi-disciplinary exercise on health across the lifespan, much remains to be done. The literature has failed to consistently or adequately report subject age group, sex, ability level, and/or event-distance specialization. The demands of training and racing are relatively unquantified. Multiple definitions and reporting methods for injury and illness have been implemented. In general, risk factors for maladaptation have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 260 publications
(212 reference statements)
2
47
0
3
Order By: Relevance
“…On the other hand, white cells are an important part of the immune system. The immune system may be affected by the level of activity in which an athlete is engaged (Vleck et al, 2014 ). Through several mechanisms, the immune system may be depressed during intense endurance activity, resulting in an increased risk of illness or infection (Knez et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, white cells are an important part of the immune system. The immune system may be affected by the level of activity in which an athlete is engaged (Vleck et al, 2014 ). Through several mechanisms, the immune system may be depressed during intense endurance activity, resulting in an increased risk of illness or infection (Knez et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In athletes, oxidative stress is a recognized causative agent of muscle redox imbalance that can promote muscle fatigue and injury, thus impairing exercise performance [ 1 , 3 , 7 , 9 ]. However, so far, a limited number of studies have focused on oxidative stress in female athletes [ 11 14 ]. A report [ 15 ] demonstrated that female athletes were more susceptible to oxidative stress than male athletes; however, this study did not evaluate contraception, a major issue to be addressed in female athletes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although up to now the demands of training and competition in an ultra-endurance race are not well described, it has been suggested that triathletes do "extreme amounts of exercises" [3]. Therefore, triathlon Ironman® distance competition can be considered suitable to be studied as a very interesting model of an extreme physiological situation able to promote the deleterious actions of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Even if many variations of the sport exist, triathlon, in its most popular form, involves swimming, cycling, and running in immediate succession over various distances [2]. Triathlon thereby provides a great opportunity to investigate the effects of multidisciplinary exercises on health, and to this aim, much remains to be done [3]. Long competitions require great power endurance possibly leading to heat stress and dehydration [4,5], muscle injury [6], oxidative stress [7,8], inflammation [9,10], immunologic alterations [11,12], and cardiac remodeling [13].…”
Section: Introductionmentioning
confidence: 99%